PENGARUH JENIS BAKTERI PROBIOTIK TERHADAP PERTUMBUHAN IKAN LELE MUTIARA YANG DIPELIHARA MENGGUNAKAN SISTEM BIOFLOK - Harits Noodin; Ita Apriani (Universitas Sriwijaya, 2021)
The main problems faced by fish farmers are waste, uneaten feed and feces. Which can reduce water quality and have a significant impact on fish growth and survival. This study aims to determine the effect of giving various types of probiotics on the growth rate and viability of Mutiara catfish raised using the biofloc system. We used Lactobacillus sp., Bacillus subtilis, and Nitrobacter as probiotic bacteria. This study used a completely randomized design experimental method with 4 treatments and 3 replications, namely K = probiotic less/control, P1= Lactobacillus probiotic, P2= Bacillus subtilis probiotic, P3= Nitrobacter probiotic. Catfish are reared for 30 days, feeding 3 times a day with FR 5% of body biomass. The parameters observed were absolute length growth, survival, Feed Conversion Ratio (FCR) and Specific Growth Rate (SGR) which were analyzed using ANOVA (P <0.05) and Duncan's test to see the differences between treatments. The results showed that the bacteria probiotic treatment had no significant effect on FCR and fish survival, but had a Lactobacillus sp significant effect on growth in absolute length (3.96 ± 0.06 cm) and the growth rate of daily specific weight (5,45±0,18 %/day). To increase the length and weight growth of catfish fry, probiotic bacteria of the type Lactobacillus sp. on cultivation media.Key words :biofloc, growth rate, lactobacillus, mutiara catfish, probiotics